Ethnomathematics Perspective and Challenge as a Tool of Mathematical Contextual Learning for Indigenous People - Nur, Andi Saparuddin; Waluya, Stevanus Budi; Kartono, Kartono; Rochmad, Rochmad (Universitas Ahmad Dahlan, 2021)
Indigenous people have a very strong connection with culture. The national curriculum needs to provide a place for student learning in indigenous people. Mathematics as knowledge applied in daily life activities becomes relevant to the culture of indigenous people. The purpose of this study is to obtain an overview related to the perspective and challenge of ethnomathematics as a contextual learning mathematics framework for indigenous people. This research is a qualitative study with an ethnographic approach and is carried out on Ammatoa indigenous people, Tana Toa Village, Kajang District, Bulukumba Regency, South Sulawesi Province. The data sources in this study were the head of the Tana Toa village, the tribal chief of Ammatoa, and the teacher in the indigenous territories. Data collection is done through observation, in-depth interviews, literature studies, and document analysis. The results of this study indicate the association of AmmatoaÂ culture with mathematical content which includes knowledge systems, traditional activities, and cultural artifacts. Domains of school mathematics content related to Ammatoa culture include; the concept of number, geometry, comparison, sequence and series, as well as probability and combinatorics. Mathematics learning in Ammatoa indigenous people needs to consider aspects of culture that involve collaborative involvement.